Determination of Mercury in Ayurvedic Dietary Supplements That Are Not Rasa Shastra Using the Hydra-C Direct Mercury Analyzer - Amir A. Abdalla; Robert E. Smith (International Journal of Analytical Chemistry)
Mercury has been determined in Ayurvedic dietary supplements (Trifala, Trifala Guggulu, Turmeric, Mahasudarshan, Yograj, Shatawari, Hingwastika, Shatavari, and Shilajit) by inductively coupled plasma-mass spectrometry (ICP-MS) and direct mercury analysis using the Hydra-C direct mercury analyzer (Teledyne Leeman Labs Hudson, NH, USA). Similar results were obtained from the two methods, but the direct mercury analysis method was much faster and safer and required no microwave digestion (unlike ICP-MS). Levels of mercury ranged from 0.002 to 56 μg/g in samples of dietary supplements. Standard reference materials Ephedra 3240 and tomato leaves that were from the National Institute of Standard and Technology (NIST) and dogfish liver (DOLT3) that was from the Canadian Research Council were analyzed using Hydra-C method. Average mercury recoveries were 102% (RSD% 0.0018), 100% (RSD% 0.0009), and 101% (RSD% 0.0729), respectively. Hydra-C method Limit Of Quantitation was 0.5 ng.